PIM1 Kinase as a Target in Prostate Cancer: Roles in Tumorigenesis, Castration Resistance, and Docetaxel Resistance - L. Holder, Sheldon; A. Abdulkadir, Sarki (Current Cancer Drug Targets, 2014)
PIM1 kinase is a serine/threonine kinase that has been shown to be overexpressed in multiple human malignancies, including prostate cancer. PIM1 phosphorylates multiple cellular substrates to inhibit apoptosis and promote cell cycle progression. Increased PIM1 can also facilitate genomic instability to promote neoplastic processes. PIM1 kinase is overexpressed in high-grade prostate intraepithelial neoplasia and in prostate cancer compared to normal prostatic tissue and benign prostate hyperplasia. Elevated PIM1 levels have been shown to be the direct result of oncogenic fusion proteins and active signal transduction pathways. In vitro and in vivo mouse studies indicate that PIM1 is weakly tumorigenic but synergizes dramatically when coexpressed with MYC. PIM1 kinase can also phosphorylate the androgen receptor (AR), thereby regulating AR degradation and function, in a low androgen environment. This finding implicates PIM1 in castration -resistant prostate cancer. Furthermore, expression of PIM1 has been shown to be increased in prostate tissue after docetaxel exposure, conferring partial resistance to docetaxel. Correlatively, decreased PIM1 levels sensitize prostate cancer cells to docetaxel treatment. Thus, PIM1 may be a target in docetaxel resistant disease. In summary, PIM1 kinase is involved in prostate tumorigenesis, castration resistance, and docetaxel resistance. Several PIM1 kinase inhibitors have been reported and are in varied stages of drug development. PIM1 is involved in multiple processes in the development and propagation of prostate cancer, thus a PIM1 kinase inhibitor may serve as an effective therapeutic agent in this prevalent disease.
Keywords: STAT